Polysemy in finite verbs according to their linguistic structure and its consequent impact on spanish-english translation - Cantorna Blanco, Rocío (2020)
Fil: Cantorna Blanco, Rocío. Pontificia Universidad Católica Argentina. Facultad de Filosofía y Letras. Departamento de Lenguas; Argentina